ESTIMATION OF GROSS REGIONAL PRODUCT ON THE BASIS OF ORGANIZATIONS FINANCIAL STATEMENTS DATA - M. Uspayeva (Вестник университета, 2016)
The article concerns the problems of regional statistics indicators formation on the basis of organizations financial statements data. In the article the features of gross regional product indicator formation based on statement data developed in accordance with IFRS principles are analyzed, estimation schemes of its elements using the profit and loss statement data of the organizations are presented.